Сумарна бальна шкала прогнозування виживаності хворих з ранніми стадіями недрібноклітинного раку легенів - Колеснік, Олексій Петрович; Шевченко, Анатолій Іванович; Лях, Ю. Є.; Гурьянов, В. Г.; Колесник, А. П.; Шевченко, А. И.; Лях, Ю. Е.; Kolesnik, O. P.; Shevchenko, A. I.; Lyakh, Y. Е.; Gurianov, V. G. (Общественная организация Украинская Ассоциация «Компьютерная Медицина» (УАКМ); Институт Медицинской информатики и Телемедицины (Институт МИТ), 2014)
Рак легені (РЛ) є одним із найпоширеніших злоякісних новоутворень (ЗН) у всьому світі. В середньому шестеро з десяти тих, що захворіли на РЛ гинуть протягом року від прогресування захворювання. Основним видом лікування, що дає надію на видужання залишається операція. Однак, навіть у 25%–60% хворих із I-ю стадією недрібноклітинного раку легенів (НДКРЛ) протягом 2-х років виникають локальні рецидиви або віддалені метастази після хірургічного втручання. Для поліпшення результатів лікування хворих з НДКРЛ необхідне виділення групи пацієнтів з несприятливим прогнозом, яким проведення ад’ювантної поліхіміотерапії (АПХТ) дозволить поліпшити виживаність. Метою нашого дослідження було створення прогностичної моделі, з метою виявлення пацієнтів з ранніми стадіями НМКРЛ та несприятливим прогнозом. Дослідження проведено у 254 хворих із ранніми стадіями НДКРЛ, що проходили лікування з червня 2008 по грудень 2012 у відділені торакальної хірургії Запорізького обласного клінічного онкологічного диспансеру. На основі комплексу покрокових статистичних методів нами була створена сумарна бальна шкала прогнозування несприятливого перебігу захворювання у хворих з ранніми стадіями НДКРЛ. На першому кроці в побудові шкали — визначення списку змінних, які є потенційними предикторами, нами було відібрано 39 змінних. Рак лёгкого (РЛ) является одним из самых распространенных злокачественных новообразований (ЗН) во всем мире. В среднем шесть из десяти, заболевших РЛ погибают в течение года от прогрессирования заболевания. Основным видом лечения, который дает надежду на выздоровление остается операция. Однако, даже у 25%–60% больных с I-й стадией немелкоклеточного рака легких (НМКРЛ) в течение 2-х лет после хирургического лечения возникают локальные рецидивы или отдаленные метастазы. Для улучшения результатов лечения больных с НМКРЛ необходимо выделение группы пациентов с неблагоприятным прогнозом, которым проведение адъювантной полихимиотерапии (АПХТ) позволит улучшить выживаемость. Цель. Целью нашего исследования было создание прогностической модели, с целью выявления пациентов с ранними стадиями НМКРЛ и неблагоприятным прогнозом. Introduction. Lung cancer is the main malignant tumor all over the word. On average, six out of ten of patients with lung cancer die within a year of disease progression. The main treatment that offers hope for survival is surgery. However, even in the 25%–60% of patients with I-th stage NSCLC within 2 years of having local recurrence or distant metastasis after surgery. To improve the outcomes of patients with NSCLC necessary discharge of patients with a poor prognosis that of adjuvant chemotherapy (APHT) would improve survival. Purpose. The aim of our study was to create a predictive model to identify patients with early-stage NSCLC with poor prognosis. Materials and methods. The study was conducted in 254 patients with early-stage NSCLC, who were treated between June 2008 and December 2012 at the Department of Thoracic Surgery Zaporozhye Regional Clinical Oncology Center. Based on a complex turnbased statistical methods we established the total point scale prediction of adverse disease course in patients with early-stage NSCLC. The first step in building scale — a list of the variables that are potential predictors we have selected 39 variables. Result and discussion. Predictors that had a statistical relationship with the dependent variable with the level of significance (p = 0,1) and fewer were still included in the regression model . As regression model was selected for optimum scaling Regression (Regression with Optimal scaling (CATREG)) (implemented in SPSS 17.0). Thus, taking into account the categorization to the regression model included 12 of the 39 potential predictors: size of tumor (cm), criterion «N», stage of disease, histological form of the tumor, surgery volume, volume of lymphdissection, intrapericardial ligation of vessels, complaint to hemoptysis, Ki-67 expression, expression of Her-2-neu, expression of EGFR, pancytokeratine expression. The last step of the scale is the practical test adequacy threshold point. It was accounted the actual rate of death from progression of NSCLC patients with a total score of 28 or less. It amounted to 8,8 ± 2,7% (about 10%). The actual rate of progress NMKRL deaths in patients with a total score of over 28 was 48,9 ± 4,2% (about 50%). Model specificity was 58,9%, sensitivity — 87,3%. Conclusion. The result of our study was to create a scale that is based on estimates of 12 signs of the patient can speak objectively about the risk of death by probability. Patients with prognostic score of more than 28 dynamic requires careful monitoring to detect early recurrence and further treatment.
Суммарная бальная шкала прогнозирования выживаемости больных с ранними стадиями немелкоклеточного рака лёгких
The total scale for prognosis of survival patients with early stages of non-small cell lung cancer
Keywords: прогностична модель; виживаність; недрібноклітинний рак легенів; прогностическая модель; выживаемост; немелкоклеточный рак лёгких; Prognostic model; Survival; Non small cell lung cancer